IMPROVING STUDENTS’ READING SKILLS THROUGH WORD GAMES TABOO WORDS MEDIA IN DESCRIPTIVE TEXT TO IMPROVE STUDENTS READING SKILLS - Nurul Afifah Musyarofah; Fitri Yulianti; M. Wahyu Widiyanto (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The objective of this research is to determine the significant difference in students reading skills before and after being introduced the word game taboo words media for seven grade students grade A at SMP N 3 Blora. The research methodology us a quantitative pre-experimental research design. The sample was 30 students, the instrument for research there were a pre-test and post-test. The researcher employed Indonesian KKM (Minimum Completeness Criteria) with the KKM score of 75 as the standard. Pre- test result were only 56,4 % met the KKM standards, and the post -test results were 78,2% accomplishing the KKM standards. The researcher also employed the Paired sample t-test to ascertain whether or not the significant difference students reading skill before and after being introduced the Word Game Taboo Words Media and to show the effectiveness improving after introduced the treatment. In this case, the paired sample t-test were 000,< 0,01. It indicates that there was a significant difference in Improving reading skill of descriptive text before and after being introduced the Word game taboo words media.